Nasal conveyance of Methicillin-resistant Staphylococcus aureus (MRSA) strains among dental professionals with varying levels of clinical exposure: A comparative study - Nandita Subba Rao; Prajna Pramod Nayak; K.V.V. Prasad (Journal of Oral Biology and Craniofacial Research)
Objective: Any control program for MRSA requires identifying the whole hospital reservoir. The likelihood of conveyance of MRSA may be higher in dental settings. Hence, the aim was to compare the nasal conveyance MRSA among dental professionals with varying levels of clinical exposure in a tertiary dental hospital in South India. Methods: A total of 81 volunteers were stratified based on the number of years of clinical exposure. The nasal swabs were subjected to catalase and coagulase tests as well as antibiotic susceptibility test. Chi- Square test was done to compare the different types of organisms isolated from dental professionals with varied levels of clinical exposure. Results: Out of the total 81 isolates, 62.96% of the isolates were MSCONS (Methicillin sensitive coagulase negative staphylococcus), 20.98% of them were MRCONS (Methicillin resistant coagulase negative staphylococcus), 9.87% were MSSA (Methicillin sensitive staphylococcus aureus) and 3.7% were MRSA positive and 2.46% were other gram negative organisms. Conclusions: MRCONS, MSSA and MRSA were shown to increase with an increase in the clinical exposure years.